Is there a role of Tau in Huntington′s disease?. Issue 1 (21st September 2016) - Zerr, Inga; Bähr, Mathias
Abstract: Alterations of the cerebrospinal fluid (CSF) composition are useful clinical diagnostic tools as well as a source of candidates for new biomarkers of neurodegenerative disorders. This Editorial highlights a study by Rodrigues and colleagues in which the authors try to establish Tau as a new biomarker for Huntington´s disease (HD). The study confirmed in two independent, age‐controlled patient populations at various disease stages, asymptomatic mutation carriers and healthy controls, that CSF total Tau concentrations in HD gene mutation carriers are increased compared with healthy controls. This is a strong evidence that CSF total Tau concentration is associated with phenotypic variability in HD. Read the highlighted article 'Cerebrospinal fluid total tau concentration predicts clinical phenotype in Huntington's disease' on page22 . Abstract : Alterations of the cerebrospinal fluid (CSF) composition are useful clinical diagnostic tools as well as a source of candidates for new biomarkers of neurodegenerative disorders. This Editorial highlights a study by Rodrigues and colleagues in which the authors try to establish Tau as a new biomarker for Huntington´s disease (HD). The study confirmed in two independent, age‐controlled patient populations at various disease stages, asymptomatic mutation carriers and healthy controls, that CSF total Tau concentrations in HD gene mutation carriers are increased compared with healthy controls. This is a strong evidence that CSF total Tau concentration is associated with phenotypic variability in HD. Read the highlighted article 'Cerebrospinal fluid total tau concentration predicts clinical phenotype in Huntington's disease' on page22 .